2021
DOI: 10.1152/ajplung.00276.2020
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of ammonia-induced acute lung injury in mice

Abstract: In this study, a genetically diverse panel of 43 mouse strains was exposed to ammonia and genome-wide association mapping was performed employing a single nucleotide polymorphism (SNP) assembly. Transcriptomic analysis was used to help resolve the genetic determinants of ammonia-induced acute lung injury. The encoded proteins were prioritize based on molecular function, nonsynonymous SNP within a functional domain, or SNP within the promoter region that altered expression. This integrative functional approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 142 publications
0
6
0
Order By: Relevance
“…Homology analyses of important differentially expressed lncRNAs have been performed to find out regions of local similarity between rat and human sequences. Some identified homologous sequences have been demonstrated in participating lung injury according to previous studies [ 16 25 ]. SNX19 had suggestive single-nucleotide polymorphism association with ammonia-induced acute lung injury and had pathophysiological roles that could be associated with acute lung injury in different ways [ 16 ].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Homology analyses of important differentially expressed lncRNAs have been performed to find out regions of local similarity between rat and human sequences. Some identified homologous sequences have been demonstrated in participating lung injury according to previous studies [ 16 25 ]. SNX19 had suggestive single-nucleotide polymorphism association with ammonia-induced acute lung injury and had pathophysiological roles that could be associated with acute lung injury in different ways [ 16 ].…”
Section: Discussionmentioning
confidence: 78%
“…Literature research has found that transcripts of homologous sequences SNX19 (corresponding with lncRNA TCONS_00009865 in rats), KCNQ1OT1 (corresponding with lncRNA TCONS_00030049 in rats), RAB1A (corresponding with lncRNA TCONS_00081686 in rats), CREB1 (corresponding with lncRNA TCONS_00091647 in rats), ABL1 (corresponding with lncRNA TCONS_00175309 in rats), RPS6 (corresponding with lncRNA TCONS_00175309 in rats), NEDD4 (corresponding with lncRNA TCONS_00255085 in rats), and FBXL2 (corresponding with lncRNA TCONS_00277162 in rats) participate in important processes of lung injury [ 16 25 ]. These lncRNAs and their homologous sequences may play an important role in intrauterine infection/inflammation-induced lung injury.…”
Section: Resultsmentioning
confidence: 99%
“…AATF has also been reported overexpressed in various cancerous tissues, including lung and colorectal cancer, as well as lymphomas [ 32 ]. A recent study revealed AATF as one of the candidate genes associated with acute lung injury [ 33 ]. It has been reported that AATF expression increases during disease progression and is involved in a pathway related to airway inflammation in COPD [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…SNX19 is essential for the lipid raft residence of D 1 R, cAMP production, and promotion of effective D 1 R signaling [20]. SNX19 also regulates the signaling of histamine receptor H4 (HRH4), a GPCR that is important in the initiation and maintenance of inflammation in mouse lung, following ammonia exposure [38].…”
Section: Snx-pxa-rgs-pxc Subfamily In Receptor Signalingmentioning
confidence: 99%
“…There is a dynamic coordinated interaction among the recycling, retrograde, and degradative pathways, which maintains normal cellular functions [2,3]. However, if the SNX-PXA-RGS-PXC subfamily, like all other SNX subfamilies, is dysfunctional and disabled to transport receptor cargoes to their appropriate cellular destinations, there will be the impairment of the above-mentioned pathways, which will negatively affect cellular functions, causing disorders, such as those listed in Table 4 [17][18][19][20]23,27,33,38,[89][90][91][92][93][94][95][96][97][98].…”
Section: Snx-pxa-rgs-pxc Subfamily In Physiology and Pathophysiologymentioning
confidence: 99%